Difficulties in process management and standardization in junior companies: a case study - Veloso Teixeira Guimarães, Rodrigo; Peron de Paula, Pablo; Fróes Couto, Felipe (Seven Editora, 2023)
Introduction/Problematization: Junior companies are environments that can provide the experience of the business student in the market, develop behavioral and technical skills and have direct contact with the professional environment. Thus, it is essential that they have robust internal processes and that they can weaken the dynamism of the environment, taking into account the challenges and difficulties encountered. In this context, the following question arises: what are the main internal management difficulties observed in the Junior Company, in view of the standardization of operational procedures? Objective/proposal: The present work sought to understand the main obstacles faced by these companies, from a single case study of Empresa Júnior Unimontes - EJU. Thus, the present work has as general objective to analyze the main difficulties of internal management of the Junior Company. In addition, as specific objectives, it is sought to: a) map the management processes; b) to identify possible improvements within the process; c) development of an instrument of reference and control of the processes monitored. Methodological Procedures: The Business Process Management Notation (BPMN) language was used as a business, modeling notation, interview and participant observation for data collection and, for the discussion of the results, the analysis of content and documentary research. Main Results: The results pointed to difficulties in the lack of BPM management, culture of continuous improvement and turnover of the managing members. Finally, despite the difficulties, these environments can provide the development of competencies within the framework of the theory of entrepreneurial and academic behavior. Final Considerations/Conclusion: It is concluded that the use of the BPM methodology made it possible to demonstrate how the collection, observation and standardization of processes can help identify the main obstacles that delay and reduce its results. Despite the difficulties encountered, the experience provided a real environment of contact with the market and the development of entrepreneurial skills. Research Contributions: This work brings as a contribution the application of management tools in the daily life of undergraduate students. The results show that the immersion of academics in junior environments promotes the development of entrepreneurial and cognitive skills, making them more innovative, adaptive and technical professionals who competitive advantage in the professional environment. DOI: https://doi.org/10.56238/tfisdwv1-149